Redes de prostitución y cotidianidad del lupanar. El oficio de prostituta desde el testimonio de María Espinoza Cabezas (Santiago de Chile, 1908) - Ignacio Ayala Cordero (Nuevo mundo - Mundos Nuevos, 2012)
From the denunciation, investigatory declarations and comparisons provided by María Espinoza in judgement against Armando Olivares for murder and other crimes, this paper gives an account of the everyday life of prostitution and social networks that creates the conditions for their development. Scanning from the “inmates” as subjects, their motivations to enter and stay in trade. The relations of authority in the brothel, trafficking in women, relationships with authority, relative legislation and how prostitutes accede to justice, are the crux of this research.